MANAJEMEN KEPEMIMPINAN KEPALA SEKOLAH DALAM MENGEMBANGKAN SARANA DAN PRASARANA UNTUK MENINGKATKAN MUTU PENDIDIKAN DI SDN POGAR III BANGIL - Ani Yanti Rosida; Taufiq Harris; Suyitno (STKIP Subang, 2025)
This study aims to analyze the leadership management of the school principal in developing educational facilities and infrastructure to improve the quality of education at SDN Pogar III Bangil. This research employed a qualitative approach with a case study design. Data were collected through in-depth interviews with the principal and teachers, direct observations of school facilities, and documentation analysis of school planning records. The findings indicate that the principal effectively performed managerial functions through participatory planning, systematic organization, gradual implementation of facility development, and continuous supervision. The improvement of educational facilities positively influenced learning comfort, student motivation, and the quality of the teaching and learning process. The main challenges encountered were limited funding and teachers’ technological competencies, which were addressed through collaboration with the school committee and internal training programs. The study concludes that effective principal leadership in managing school facilities and infrastructure plays a significant role in enhancing educational quality at the elementary school level.